Snakes and Ladders Game Method and Flashcards on Knowledge, Attitudes and Skills of Karang Taruna Youth Regarding Basic Life Support - Aan Dwi Sentana; Sitti Rusdianah Jafar; Moh. Hasbi; Desty Emilyani; Lale Wisnu Andrayani; Dewi Purnamawati; Mardiatun; Gusti Ngurah Anom (Postgraduate, University of Mataram, 2025)
The growing understanding of the importance of Basic Life Support (BLS) training among adolescents in organized communities has given rise to the need to implement engaging learning methods. This study aims to determine the effectiveness of the Snakes and Ladders and Flashcard game methods on the knowledge, attitudes, and skills of adolescents in Karang Taruna in Babussalam Village. The method used was the Pre-Experimental One Group Pretest Posttest design, with 64 adolescents as respondents taken through stratified random sampling. Data were collected through questionnaires and observations and analyzed using the Wilcoxon Signed Rank Test. The results showed that there was a significant increase in the level of knowledge (from 4.48 to 9.56, p < 0.001), attitudes (from 22.55 to 37.95, p < 0.001), and skills (from 0 to 5.83, p < 0.001) after the implementation of the intervention. These results confirm that the game and visualization methods help in improving BLS understanding and skills. In conclusion, the use of the Snakes and Ladders and Flashcard game methods is effective in improving adolescent knowledge, attitudes, and skills, thus contributing to improving community health capacity in Babussalam Village. This study recommends the application of similar interactive methods in other health training programs to strengthen the appeal and effectiveness of learning.